2005
DOI: 10.1074/jbc.m500885200
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of Baculovirus RNA Triphosphatase Complexed with Phosphate

Abstract: Baculovirus RNA 5 -triphosphatase (BVP) exemplifies a family of RNA-specific cysteine phosphatases that includes the RNA triphosphatase domains of metazoan and plant mRNA capping enzymes. Here we report the crystal structure of BVP in a phosphatebound state at 1.5 Å resolution. BVP adopts the characteristic cysteine-phosphatase ␣/␤ fold and binds two phosphate ions in the active site region, one of which is proposed to mimic the phosphate of the product complex after hydrolysis of the covalent phosphoenzyme in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 37 publications
0
35
0
Order By: Relevance
“…Here we refer to it by the hybrid name ptp/bvp. Crystallographic studies of PTP/BVP showed that its structure was similar to metazoan RNA capping enzymes, thus confirming its specificity for RNA substrates (5). Furthermore, in vivo analyses showed that PTP/ BVP could substitute for yeast RNA triphosphatase in the cap synthetic pathway in yeast cells (42).…”
mentioning
confidence: 71%
“…Here we refer to it by the hybrid name ptp/bvp. Crystallographic studies of PTP/BVP showed that its structure was similar to metazoan RNA capping enzymes, thus confirming its specificity for RNA substrates (5). Furthermore, in vivo analyses showed that PTP/ BVP could substitute for yeast RNA triphosphatase in the cap synthetic pathway in yeast cells (42).…”
mentioning
confidence: 71%
“…The phosphatase core consists of a central five-stranded β-sheet (β1−β5) (highlighted with a light blue background in Figure 2B) sandwiched between two clusters of five (h1–h5) and four (h6–h9) helices that make contacts with the solvent (Figure 2B). A search using the Dali server 40 identified baculovirus BVP (PDB entry 1YN9) 21 and the RNA 5′-phosphatase domain of the mouse mRNA capping enzyme (PDB entry 1I9S) 41 as the phosphatases that were most structurally similar to PIR1-core (rmsds of 1.4 and 1.5 Å, respectively). PIR1-C152S-core can also be superimposed on VH1 (PDB entry 3CM3) (Figure 2C) and VHR (PDB entry 1VHR) with rmsds of 2.5 and 2.2 Å, respectively, but presents four noticeable differences from the classical VH1-like DSP-core (colored red in Figure 2B,C).…”
Section: Resultsmentioning
confidence: 99%
“…Cysteine phosphatase structures often contain phosphate(s) 12 or sulfate(s) 38 within a positively-charged pocket that includes the HCxxGxxR motif; sulfate presumably substitutes for the physiological phosphate. Two sulfate groups were observed in the catalytic site cavity of At1g05000, suggesting the possibility that a multiply phosphorylated physiological substrate may be recognized by the active site.…”
Section: Discussionmentioning
confidence: 99%
“…Two sulfate groups were observed in the catalytic site cavity of At1g05000, suggesting the possibility that a multiply phosphorylated physiological substrate may be recognized by the active site. Sulfates/phosphates in At1g05000 and in the baculovirus BVP 12 and human VHR 38 enzymes are rather distant (>3 Å) from the cysteine of the cysteine phosphatase active site motif, bringing their physiological relevance into doubt.…”
Section: Discussionmentioning
confidence: 99%